Determination of trace elements in water samples by k0 based instrumental neutron activation analysis using sodium as comparator - Mendoza, Pablo (2003)
Neutron Activation Analysis in liquid samples has been a challenge for our laboratory due to the following difficulties: i) to irradiate samples in the polyethylene vials avoiding pressure build up ii) to get an appropriate geometry for irradiation and measurement of liquid samples, and iii) to avoid excessive manipulation of samples. This work shows the development of the method for multi-element trace determination in water samples using k0 based instrumental neutron activation analysis using sodium as comparator. Samples are concentrated by evaporation in a microwave oven under controlled temperature and irradiated in aqueous solution for short lived radionuclides determination and in pellets for medium and long lived radionuclides determination. The sodium standard was prepared either liquid or solid for the corresponding analysis. After certain decay time it is possible to quantify a group of elements with sufficient sensitivity and accuracy as shown by the analysis of the standard reference material NRCC SLRS-2. This method has been satisfactorily applied for monitoring natural water samples from Lima city and other locations in Peru.